Analisis Kebutuhan Udara Dan Sistem Ventilasi Pada Tambang Batubara Bawah Tanah Lubang CBP 02 PT. Cahaya Bumi Perdana, Kota Sawahlunto, Sumatera Barat. - Annisa Oktavianingsih; Bambang Heriyadi (Journals Mining Engineering : Bina Tambang, 2021)
Abstract. PT. Cahaya Bumi Perdana is an underground coal mining company located in the village district of Parambahan, Sawahlunto, West Sumatera province. Underground mine hole in CBP 02 PT. Cahaya Bumi Perdana uses one main blower with a blow system. Hole CBP 02 is a new opening with a lenght of 80 meters. In hole CBP 02 there is one active working unit and two control tanks and one mining branch that is not yet active. From the research results, it was found that the air quality and mining gas were in quite good condition, but the temperature value had passed the established threshold, namely <85 %. This study analyzed the quality of air and gas in underground mines based on KEPMEN 1827 K/30/MEM/2018.Ventilation planning for the future is to use a suction ventilation system that is placed in the ventilation holes located between the inlets C2A and C2B with a relay blower arrangement. Installation of a suction blower followed by the installation of a blower so that the dirty air is circulated out immediately. Dirty air resulting from mining activities from one hole is sucked out throught the ventilation holes and replaced with clean air that enters throught holes C2A and C2B where the blower has been installed. Because of the CBP hole 01 is located above the CBP 02 hole, the amount of methane gas emissions will increase. From the calculation results, the air requirement in hole C2A is 27,425 m3 /s, in hole C2B is 22,735 m3 /s, and the air requirement to dilute methane gas from hole CBP 01 is 69,92 m3 /s. Then the total amount of air needed is 120,08 m3 /s. The number of blowers needed in hole C2A is 15 auxillary blowers with a capacity of 2,7 m3 /s and using 12 auxiliary blowers in hole C2B with a capacityof 2,7 m3 /s, and to remove dirty air using 6 suction fan blower. This ventilation modelling uses ventsim visual 5.Keywords : Temperature, Humadity, Blower, Ventsim Visual 5